Mathematical Modelling of Antimicrobial and Heavy Metal Resistance in Bacterial Populations Within the Flow of Agricultural Slurry in a UK Dairy Farm - Todman, Henry (2023)
Antimicrobial resistance (AMR) is a one of the most important global public health problems facing the modern era. Dairy cattle represents one of the largest agricultural industries, with approximately 265 million dairy cows across the globe. These are estimated to produce 3 billion tonnes of manure each year. Dairy slurry represents a major source for environmental contaminations of antimicrobial resistance genes (ARG). The management and storage systems of dairy slurry provide a setting in which bacteria, antibiotic residues, metals and chemicals to mix and may be a locus for selection of AMR. Mathematical modelling offers a powerful tool to explore the impact that changes to farm management practices may have on AMR dynamics, where it would be impossible to empirically explore such changes on a working farm.